Penilaian Siswa SMK Yuppentek 3 Balaraja Tangerang Berbasis Web Sebagai Media Informasi - Wahyu Hidayat; Dede Cahyadi; Deny Arbiyanto (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2021)
Information technology is increasing so fast that computers are widely used in everyday society, including in education, computers are needed. With the rapid increase in information, information media is very important because it is one of the tools to collect and rearrange information so that it becomes useful material for recipients of information. Many teachers have difficulty in giving grades because they are still in manual form so it takes a long time to provide grades using Microsoft Excel, thus making an assessment system is needed as a medium of information for students and teachers. So that teachers can more easily input grades and students can immediately see the value. The system to be designed in this assessment facility maker uses the web, UML (Unified Modeling Language), PHP, MYSQL and Black Box testing with the SWOT analysis method (Strenghts Weakness Opportunities Threats).